The Fireside Treasury of Light: An Anthology of the Best in New Age Literature - Kelly, Mary Olsen (New York Simon and Schuster Inc, 1990)
The Fireside Treasury of Light contains excerpts from the most important and meaningful books in the New Age--books that have changed peoples lives, books that have profoundly affected our society, books that have set the courses of our thinking in new and exciting directions. Writers, thinkers, poets, spiritual masters, humanistics psychologists, revolutionaries, and shamans join here to give an indication of the diverse and varied elements of New Age thinking.
Keywords: Fiction